Ulnar Head or Total Distal Radioulnar Joint Replacement, Isolated and Combined with Total Wrist Arthroplasty: Midterm Results - Gvozdenovic, Robert; Boeckstyns, Michel; Merser, Søren (Journal of Wrist Surgery, 2020)
Purpose Various implants have been described for ulnar head replacement (UHR) or for total replacement of the distal radioulnar joint (DRUJ). Many series are small and few reports on mid- or long-term results. This study is primarily aimed to report on the midterm results after ulnar head only and total DRUJ replacement using the uHead in the treatment of painful disorders of the DRUJ. The secondary aim of the study was to eventually assess the combination of UHR and total wrist arthroplasty (TWA).Materials and Methods We included 20 consecutive patients in whom an UHR with the uHead was performed at our institution between February 2005 and March 2017. There were 6 men and 14 women with mean age of 59 years (range: 36–80 years). The mean follow-up time was 5 years (range: 2–15 years). Data were recorded prospectively before operation and at follow-up examinations and entered in a registry. The patients were followed-up at 3 and 6 weeks and 3, 6, and 12 months postoperatively and thereafter annually. In five cases, the uHead was implanted simultaneously with a Remotion TWA. In four cases, a Remotion TWA had been implanted previously. Kaplan–Meier survival analysis was used to estimate the cumulative probability of remaining free of revision. A nonparametric Wilcoxon's signed-rank test was used for comparing data not normally distributed (qDASH [quick disabilities of the hand, shoulder, and arm] scores), and the paired parametric Student's t-test was used for normally distributed data (pain and visual analogue scale [VAS] scores, range of motion, and grip strength). Significance was set at a p-value of less than 0.05.Results Pain, grip strength, and the function improved significantly. Pain after surgery decreased with 50 points on the VAS score scale of 100, from 66 (mean), preoperatively (range: 16–97) to 16 (mean; range: 0–51), postoperatively, while grip strength nearly doubled from 12 KgF (mean; range: 4–22), before to 21 KgF (mean; range: 6–36), after the surgery. Patients function measured with qDASH scores improved from 56 (mean; range: 36–75), preoperatively to 19 (mean; range: 4–47), postoperatively. Wrist extension, flexion, and ulnar and radial deviation did not change to a clinically or statistically significant extend, neither did supination nor pronation improved after surgery. While three UHRs were revised early because of pain problems and/or unsatisfactory forearm rotation in two cases and infection in one, 17 had an uncomplicated postoperative course and these patients were satisfied with the results of the surgery at all the follow-ups. Due to limited number of cases, the calculation of significance in comparing combined cases with UHR only cases was abandoned.Conclusion Ulnar head arthroplasty (uHead) showed significant improvement in pain, grip strength, and the function of the patients with a painful disability of the DRUJ, without impairment on mobility on the midterm follow-up. The overall implant survival over the time and the complication rate was acceptable.
Keywords: ulnar head arthroplasty; DRUJ prosthesis; total wrist arthroplasty; ulnar head prosthesis; uHead prosthesis